2013
DOI: 10.1038/srep02002
|View full text |Cite
|
Sign up to set email alerts
|

Winter food provisioning reduces future breeding performance in a wild bird

Abstract: Supplementation of food to wild birds occurs on an enormous scale worldwide, and is often cited as an exemplar of beneficial human-wildlife interaction. Recently it has been speculated that winter feeding could have negative consequences for future reproduction, for example by enabling low quality individuals to recruit into breeding populations. However, evidence that winter feeding has deleterious impacts on reproductive success is lacking. Here, in a landscape-scale study of blue tits (Cyanistes caeruleus) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 38 publications
(61 reference statements)
0
77
1
Order By: Relevance
“…Variation in supplementary food consumption was linked to a number of demographic traits at the individual level, but at this level, we found no evidence of carry-over effects of winter seed consumption on reproductive success. Our results suggest that negative effects of supplementary feeding demonstrated previously (Harrison et al 2010, Plummer et al 2013a may have arisen through increased food availability influencing population demography, for example increasing the survival of low-quality individuals and potentially increasing resource competition during the breeding season. Additionally, temporally limiting the availability of supplementary food, as we did here, and which might occur in garden environments, may also prevent the development of carry-over effects.…”
Section: Discussionmentioning
confidence: 66%
“…Variation in supplementary food consumption was linked to a number of demographic traits at the individual level, but at this level, we found no evidence of carry-over effects of winter seed consumption on reproductive success. Our results suggest that negative effects of supplementary feeding demonstrated previously (Harrison et al 2010, Plummer et al 2013a may have arisen through increased food availability influencing population demography, for example increasing the survival of low-quality individuals and potentially increasing resource competition during the breeding season. Additionally, temporally limiting the availability of supplementary food, as we did here, and which might occur in garden environments, may also prevent the development of carry-over effects.…”
Section: Discussionmentioning
confidence: 66%
“…A similar study on the same species (Plummer et al 2013a) proved that quality of food provided during winter is also important, as fat provision had negative effects on egg quality in the subsequent breeding season, whereas this effect was mitigated when fat was amended with vitamin E. A possible explanation for this result is that birds may have become dependent on such easily accessible, energy-rich food source; though it may have enhanced their overwinter survival, it reduced their dietary diversity, leading to that they failed to build up reserves of key nutrients important in egg formation. In a follow-up study with the same design (Plummer et al 2013b) fat supplement had similarly no effect on clutch size, but had detrimental effects on the number, weight and size of fledged young. In a three-year long study of woodland great tits and blue tits, several week long food supplementation until hatching yielded some surprising outcome, as the authors found reduction in both clutch size and number of hatched young in the treated groups (Harrison et al 2010).…”
Section: Changes In Resource-based Forcesmentioning
confidence: 93%
“…in the House Sparrow (Peach et al 2008. Nestling size also strongly predicts later fledging success in the Great Tit (Plummer et al 2013b), and size prior to fledging is known to be a good predictor of later recruitment as a breeding adult in many bird species (Schwagmeyer & Mock 2008). Thus, the quantity and/or quality of nestling food is one of the most crucial factors for chicks, as early nutritional conditions strongly affect both their survival and development.…”
Section: Seress G and Liker Amentioning
confidence: 99%
“…Nonetheless, urban environments are linked to reductions in fitness and health in a substantial number of organisms (Chamberlain et al, 2009;Murray et al, 2015). Hence, urban habitats are sometimes considered ecological traps which attract organisms, for example by anthropogenic food availability, but are insufficient for supporting successful rearing of offspring (Plummer et al, 2013;Sumasgutner et al, 2014;Lamb et al, 2017). There is a need, therefore, to understand the mechanisms by which urbanization reduces reproductive success.…”
Section: Introductionmentioning
confidence: 99%